TELEMEDICINE IN ORTHODONTICS: THE REMOTIZATION OF ORTHODONTIC RECORDS FOR DIAGNOSIS AND THERAPY - Gianluigi Caccianiga; Claudia Crestale; Paolo Zorzella; Dorina Lauritano; Alessandra Cantu; Marco Baldoni (European Scientific Journal, ESJ, 2013)
Objective: Aim of this study was to assess the effectiveness of Dental Centers connected to each other managing orthodontic records. The secondary aim was to carry out epidemiological studies and to evaluate their compliance with local health policies.Methods: Cloud Computing Technology and Video chat systems were used. Epidemiologic data from four orthodontic Centers were collected. Prevalence of the skeletal class and the IOTN (Index of Orthodontic Treatment Need) were determined.Results: Tele epidemiology provided a sample of 1501 patients. 7% presented skeletal class III and 36 % skeletal class II. The IOTN Index was grater in Clinic of Monza and Bergamo than the other Centers.Conclusions: Cloud and Video chat systems are fundamental tools for improving efficiency in Tele Orthodontics. Epidemiological studies are useful for manage the Dental Centers and for planning health policies regarding prevention, education and economic support.